2016
DOI: 10.1007/8904_2016_9
|View full text |Cite
|
Sign up to set email alerts
|

Paracentric Inversion of Chromosome 21 Leading to Disruption of the HLCS Gene in a Family with Holocarboxylase Synthetase Deficiency

Abstract: Holocarboxylase synthetase (HLCS) deficiency is a rare autosomal recessive disorder that presents with multiple life-threatening metabolic derangements including metabolic acidosis, ketosis, and hyperammonemia. A majority of HLCS deficiency patients respond to biotin therapy; however, some patients show only a partial or no response to biotin therapy. Here, we report a neonatal presentation of HLCS deficiency with partial response to biotin therapy. Sequencing of HLCS showed a novel heterozygous mutation in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…For example, Donti et al have revealed five cases of HLCS deficiency with broad differences in initial presentation and phenotype, and they have also described six novel pathogenic variants: c.500A > C (p.Tyr167Ser), c.1532A > T (p.Asn511Ile), c.2078G > C (p.Gly693Ala), c.977G > A (p.Gly326Glu), c.1710C > G (p.Asn570Lys), and c.1519 + 5G > A [9]. In addition, Quinonez et al have identified the novel heterozygous variant c.996G > C (p.Gln332His) and a paracentric inversion on chromosome 21 by utilizing cytogenetic analysis [10]. In this study, we investigated a Chinese Han pedigree with HLCS deficiency and described the relationship between molecular mutation and clinical manifestation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Donti et al have revealed five cases of HLCS deficiency with broad differences in initial presentation and phenotype, and they have also described six novel pathogenic variants: c.500A > C (p.Tyr167Ser), c.1532A > T (p.Asn511Ile), c.2078G > C (p.Gly693Ala), c.977G > A (p.Gly326Glu), c.1710C > G (p.Asn570Lys), and c.1519 + 5G > A [9]. In addition, Quinonez et al have identified the novel heterozygous variant c.996G > C (p.Gln332His) and a paracentric inversion on chromosome 21 by utilizing cytogenetic analysis [10]. In this study, we investigated a Chinese Han pedigree with HLCS deficiency and described the relationship between molecular mutation and clinical manifestation.…”
Section: Introductionmentioning
confidence: 99%